MEANING ANALYSIS OF ENGLISH SLOGANS ADVERTISEMENT - Eva Nurul Chandra (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2013)
This study intends to analyse the text meaning of the slogan. As we know, the usage of the word in slogan text is so meaningful. Sometimes the meaning of the word in slogan has a figurative meaning and commercial purposes. The writer uses 30 kinds of English slogan as the object of the research, 7 slogans come from the advertisements that serve a service and 23 slogans come from the advertisements that serve a product. In this research, the writer uses the qualitative method. The collected data of English slogans advertising from the English newspapers or English magazines are analyzed qualitatively based on related theory or approaches, such as Semantics and stylistics.From 30 kinds of slogan, the writer finds 7 slogans that not contain a figurative language. Usually the producer uses an ordinary word in making their slogan. So the meaning can be understood from its denotation. There are 8 slogans that use hyperbole as a figurative language in order to describe the product.Key Words: Slogans, advertisements, figurative meanings, semantics, stylistics